Studi Perencanaan Dinding Penahan Tanah Tipe Gravitasi pada Jalan Brigjen Abdul Manan Wijaya Kecamatan Pujon Kab. Malang - Jalang, Yosef (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
The retaining wall is a component of the main building structure for highways and other environmental buildings that relate to contoured land or land that has different elevations. Briefly the retaining wall is a wall built to hold the soil mass above the structure or building that is made. There are several types of retaining walls that are often used in the field of building construction such as gravity retaining walls, cantilever retaining walls, counterfort retaining walls, and butters retaining walls. The purpose of this research is to analyze the stability of the rolling force, shear and soil carrying capacity. The dimensions of this retaining wall were built with a length (b) 22 meters and height (h) = 7 meters, base width (B) = 5 meters, normal water surface conditions without earthquakes, stability against bolster force = 1.7> 1.5 ( safe), shear force = 1.7> 1.5 (safe), flood water surface conditions without earthquake, stability against bolster force = 1.6> 1.5 (safe), shear force = 1.7> 1, 5 (safe) and soil support force = 250.6 <qa = 7174.42 (safe). The retaining wall is planned to require Rp. 126,000,000.00 / m3.